2019
DOI: 10.1111/1471-3802.12479
|View full text |Cite
|
Sign up to set email alerts
|

Development of pre‐service teachers' self‐efficacy beliefs and attitudes towards inclusive education through first teaching experiences

Abstract: We examined the development of pre‐service teachers' self‐efficacy beliefs and attitudes towards inclusive education through first teaching experiences during a 4‐week practicum. Additionally, we assessed the burnout‐related variables (job‐related satisfaction and exhaustion and perceived competence support during the practicum). Whereas t‐tests for paired samples showed that self‐efficacy increased significantly, attitudes remained the same except for a decrease regarding attitudes towards the effects of incl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
20
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 32 publications
(22 citation statements)
references
References 48 publications
(72 reference statements)
1
20
1
Order By: Relevance
“…Varcoe and Boyle (2014) argued that PT's attitudes may be more influenced by their perceptions of matters of classroom practices, such as the availability of resources and support, rather than by any biases toward including students with special needs. In contrast, Weber andGreiner's (2019) study (2019) has revealed a low, but significant, positive relationship between positive experiences during teaching field experiments and attitudes toward inclusive education.…”
Section: Influence Of Pre-service Teachers' Contextual Characteristicsmentioning
confidence: 95%
“…Varcoe and Boyle (2014) argued that PT's attitudes may be more influenced by their perceptions of matters of classroom practices, such as the availability of resources and support, rather than by any biases toward including students with special needs. In contrast, Weber andGreiner's (2019) study (2019) has revealed a low, but significant, positive relationship between positive experiences during teaching field experiments and attitudes toward inclusive education.…”
Section: Influence Of Pre-service Teachers' Contextual Characteristicsmentioning
confidence: 95%
“…The primary effects, which advocates that teachers generally place inspirational content at the beginning to improve the quality of teaching and students' interest in learning, can affect the positive experiences, self-e cacy and attitudes [30]. The KoPa WiFi EDU system on tablets used as an assistant tool for pathological teaching in this study is a common tool in the current information era and is easy for students to master.…”
Section: Discussionmentioning
confidence: 98%
“…Teachers' attitudes towards inclusion are a significant factor in its success (Goddard and Evans, 2018; AlMahdi and Bukamal, 2019). This is especially true for pre‐service teachers, who are responsible for implementing successful inclusive education in the future (Weber and Greiner, 2019; Byra and Domagała‐Zyśk, 2021). Attitudes may either overcome prejudices or contribute to maintaining them (Byra and Domagała‐Zyśk, 2021).…”
Section: Introductionmentioning
confidence: 99%